The Responsibility of the Regional Government in Flood Management to Realize a Healthy Environment in Palembang - Yuliusman, Yuliusman; Barkah, Qodariah; Kencana, Ulya (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the juridical aspects of the local government’s role and responsibility in addressing flooding in Palembang City based on Law Number 32 of 2009 concerning Environmental Protection and Management. The issue arises from the weak implementation of regional policies in realizing the community’s right to a good and healthy environment. The study aims to analyze the conformity of local government accountability with the principles of environmental justice and sustainability. The research employs a normative legal method using statutory, conceptual, and case approaches, analyzed qualitatively. The findings indicate that although several regulations govern environmental management and disaster mitigation, their implementation remains suboptimal due to poor institutional coordination and weak law enforcement. The study concludes that strengthening the local government’s legal responsibility and policy enforcement is essential to ensure the protection of the right to a healthy and sustainable environment.   [Penelitian ini membahas aspek yuridis peran dan tanggung jawab pemerintah daerah dalam penanganan banjir di Kota Palembang berdasarkan Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Permasalahan muncul karena masih lemahnya implementasi kebijakan daerah dalam mewujudkan hak masyarakat atas lingkungan hidup yang baik dan sehat. Penelitian ini bertujuan menganalisis kesesuaian pelaksanaan tanggung jawab hukum pemerintah daerah dengan prinsip keadilan lingkungan dan keberlanjutan. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kasus, yang dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa meskipun terdapat berbagai regulasi yang mengatur pengelolaan lingkungan dan mitigasi bencana, implementasinya belum optimal karena keterbatasan koordinasi antarinstansi dan lemahnya penegakan hukum. Kesimpulannya, dibutuhkan penguatan peran pemerintah daerah dalam kebijakan dan penegakan hukum lingkungan untuk menjamin perlindungan hak atas lingkungan hidup yang sehat dan berkelanjutan.]